Subclinical progression of systemic sclerosis-related cardiomyopathy. (1st November 2020) - Stronati, Giulia; Manfredi, Lucia; Ferrarini, Alessia; Zuliani, Lucia; Fogante, Marco; Schicchi, Nicolò; Capucci, Alessandro; Giovagnoni, Andrea; Russo, Antonio Dello; Gabrielli, Armando; Guerra, Federico
Abstract : Aims: Cardiac involvement in patients with systemic sclerosis (SSc) is frequent and represents a negative prognostic factor. Recent studies have described subclinical heart involvement of both the right ventricle (RV) and left ventricle (LV) via speckle-tracking-derived global longitudinal strain (GLS). It is currently unknown if SSc-related cardiomyopathy progresses through time. Our aim was to assess the progression of subclinical cardiac involvement in patients with SSc via speckle-tracking-derived GLS. Methods: This was a prospective longitudinal study enrolling 72 consecutive patients with a diagnosis of SSc and no structural heart disease nor pulmonary hypertension. A standard echocardiographic exam and GLS calculations were performed at baseline and at follow-up. Results: Traditional echocardiographic parameters did not differ from baseline to 20-month follow-up. LV GLS, despite being already impaired at baseline, worsened significantly during follow-up (from –19.8 ± 3.5% to –18.7 ± 3.5%, p  = .034). RV GLS impairment progressed through the follow-up period (from –20.9 ± 6.1% to –18.7 ± 5.4%, p  = .013). The impairment was more pronounced for the endocardial layers of both LV (from –22.5 ± 3.9% to –21.4 ± 3.9%, p  = .041) and RV (–24.2 ± 6.2% to –20.6 ± 5.9%, p  = .001). A 1% worsening in RV GLS was associated with an 18% increased risk of all-cause death or major cardiovascular event ( p  = .03) and with a 55% increased risk of pulmonary hypertension ( p  = .043). Conclusion: SSC-related cardiomyopathy progresses over time and can be detected by speckle-tracking GLS. The highest progression towards reduced deformation was registered for the endocardial layers, which supports the hypothesis that microvascular dysfunction is the main determinant of heart involvement in SSc patients and starts well before overt pulmonary hypertension.